The development of the human vaginal fornix and the portio cervicis. Issue 7 (27th February 2021) - Fritsch, Helga; Auer, Ramona; Hörmann, Romed; Pechriggl, Elisabeth; Regauer, Sigrid; Reich, Olaf
Abstract: Introduction: One of the transitional zones of the human body is situated in the cervix uteri. The developmental differentiation of epithelial and stromal characteristics in such a region is of high clinical interest. However, few studies have focused on the development of this region, and information in anatomical and clinical textbooks is limited. We therefore examined the development of the human vaginal fornix and the cervix uteri during prenatal development. Materials and Methods: We examined 29 female embryos and fetuses between 20 and 34 weeks and two newborns using histology and immunohistochemistry. Results: The characteristic shape of the portiocervicis and the vaginal fornix first became visible in mid‐term fetuses because of the different muscular coats and of an uncategorized Müllerian‐derived epithelium, which was rapidly replaced by a multilayered squamous epithelium. Only thereafter, in older fetuses, were there organogenetic differentiation of the epithelia and the underlying stroma of the cervical canal. UGS‐derived p63/CK17‐positive cells could be identified as precursor cells for the squamous epithelium, and Müllerian‐derived CK7‐positive cells for the columnar‐type epithelium. Both cell types and different stromal zones were already present in a prenatal transformation zone. Initial functional differentiation could be observed in perinatal stages. Conclusions: Our results on prenatal human development strongly support the view that two different cell lineages meet at the transitional zone of the cervix uteri and that these lineages depend on alternative signals from the underlying stromal compartment.